Adsorbent based on X molecular sieve and preparation and application thereof

In the preparation process of X molecular sieve adsorbent, mesoporous pores are formed by using alkali treatment and ion exchange technologies such as ammonium salt solution, which solves the problems of mesoporous pore blockage and micropore damage in the prior art, and achieves efficient adsorption separation performance and compressive strength.

CN119909646APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411466241.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-31
Filing Date
2024-10-21
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing multi-stage pore X molecular sieve can easily cause mesopores to be blocked during the molding process and lose the advantage of mass transfer. Hydrothermal or acid treatment will destroy the microporous channel and reduce the adsorption capacity and compressive strength.

Method used

After mixing the X molecular sieve with the binder and calcining, the alkali treatment is carried out in situ crystallization, and then ion exchange and calcining of the ammonium salt solution is carried out to form mesoporous channels, while maintaining the stability of the molecular sieve skeleton structure.

Benefits of technology

The adsorbent has high microporous pore capacity, adsorption capacity and compressive strength, and exhibits good adsorption selectivity and good mass transfer properties when used for adsorption and separation of xylene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005093406810000151
    Figure BDA0005093406810000151
  • Figure BDA0005093406810000161
    Figure BDA0005093406810000161
  • Figure BDA0005093406810000162
    Figure BDA0005093406810000162
Patent Text Reader

Abstract

The invention relates to an adsorbent based on an X molecular sieve as well as preparation and application thereof, a preparation method of the adsorbent comprises the following steps: 1) mixing the X molecular sieve with a binder, molding and roasting to obtain a molded body; (2) treating the molded body obtained in the step (1) with an alkali solution to perform in-situ crystallization on the binder in the molded body so as to obtain a crystallized product; (3) carrying out ion exchange on the crystallized product obtained in the step (2) by using an ammonium salt solution, and roasting in a flowing atmosphere to obtain a roasted product; and 4) performing barium ion exchange and optional potassium ion exchange on the roasted product obtained in the step 3), and then drying to obtain the adsorbent. The adsorbent has mesoporous channels, simultaneously has relatively high micropore volume, adsorption capacity and compressive strength, and shows relatively good adsorption selectivity and good mass transfer performance when being used for adsorbing and separating p-xylene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of adsorption separation, and in particular to an adsorbent based on X molecular sieve and its preparation and application. Background Art

[0002] Aromatic monomers are an important type of petrochemical basic raw material with high product added value. They can be widely used in the production of polyester, pesticides, medicines and other fields. In industrial production, adsorption separation technology is mostly used to separate aromatic monomers from aromatic mixtures. The most widely used scenario for this technology is the separation of paraxylene from mixed C8 aromatics. Through the simulated moving bed process, the mixed C8 aromatics and the adsorbent are repeatedly subjected to mass transfer exchange to enrich paraxylene in the adsorbent, and then high-purity paraxylene is obtained through desorption and distillation operations. Among them, the preparation of high-performance adsorbents is the key to obtaining high-purity paraxylene products.

[0003] The active component used as adsorbent for the adsorption and separation of paraxylene in industry is mostly X molecular sieve. X molecular sieve is mixed evenly with clay as a binder in a certain proportion, and adsorbent pellets are obtained after ball rolling, drying, roasting and cation exchange. Adsorption capacity and mass transfer performance are important indicators for evaluating adsorbents. Higher adsorption capacity and good mass transfer performance are conducive to obtaining high-purity paraxylene products.

[0004] In order to improve the adsorption capacity of the adsorbent, the industry often uses an in-situ crystallization method to convert the binder into a crystal. CN1275926A discloses a coalesced molecular sieve adsorbent, the active component of which is an X molecular sieve with a Si / Al atomic ratio of 1-1.15, and the binder is a molecular sieve-able clay. After alkali treatment, the clay can be converted into an X molecular sieve, thereby improving the adsorption capacity.

[0005] Hierarchical molecular sieve materials have two types of pore structures, micropores and mesopores, and have unique advantages in mass transfer capacity, so they have great application prospects in the field of adsorption separation. However, when the hierarchical molecular sieve X is used as the active component of the adsorbent, during the molding process, the adsorbent beads are treated with alkali to crystallize in situ, which often causes secondary crystallization of the mesopores in the hierarchical molecular sieve, thereby being blocked and losing its mass transfer advantage. After molding, the adsorbent beads are hydrothermally or acid-treated to form mesopores, which will excessively damage its micropores and greatly reduce its adsorption capacity and compressive strength.

[0006] Therefore, there is still an urgent need for an adsorbent with better mass transfer capability, high adsorption capacity and high compressive strength. Summary of the invention

[0007] The purpose of the present application is to provide an adsorbent based on X molecular sieve and its preparation and application, wherein the adsorbent has mesoporous channels and has high micropore volume, adsorption capacity and compressive strength, and exhibits good adsorption selectivity and good mass transfer performance when used for the adsorption separation of xylene.

[0008] In order to achieve the above object, on the one hand, the present application provides a method for preparing an adsorbent based on X molecular sieve, comprising the following steps:

[0009] 1) mixing the X molecular sieve with a binder, forming and calcining to obtain a formed body;

[0010] 2) treating the molded body obtained in step 1) with an alkaline solution to in-situ crystallize the binder therein to obtain a crystallized product;

[0011] 3) performing ion exchange on the crystallized product obtained in step 2) with an ammonium salt solution, and calcining the product under a flowing atmosphere to obtain a calcined product; and

[0012] 4) The calcined product obtained in step 3) is subjected to barium ion exchange and optionally potassium ion exchange, and then dried to obtain the adsorbent.

[0013] On the other hand, the present application provides an adsorbent based on X molecular sieve, comprising 98.0-99.0 mass% of X molecular sieve and 1.0-2.0 mass% of matrix, and the adsorbent has a micropore volume of 0.18-0.30 mL / g, a mesopore volume of 0.01-0.1 mL / g, a mesopore maximum pore size of 2.0-8.0 nm, a 250N compressive crushing rate of less than 5.5%, and a basic bulk density of 0.91-1.20 g / cm 3 .

[0014] Preferably, at least part of the cationic sites of the X molecular sieve are occupied by barium and / or potassium ions, and the Ba content in the adsorbent calculated as BaO is 39.0-41.0 mass %, and the K content calculated as K2O is 0-3.0 mass %, based on the weight of the adsorbent.

[0015] More preferably, using 29 Si and 27 According to Al high-resolution magic angle nuclear magnetic resonance measurement, the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in the skeleton structure of the adsorbent accounts for a relative content of no less than 60 mol% of the total silicon species, and the relative content of non-skeleton aluminum accounts for no more than 5 mol% of the total aluminum species.

[0016] In yet another aspect, there is provided use of the adsorbent of the present application for adsorption separation of para-xylene.

[0017] The preparation method of the adsorbent based on X molecular sieve of the present application realizes the breaking and cutting of Si-O-Al bonds of the molecular sieve part by ammonium treatment and roasting, thereby generating mesoporous channels in the molecular sieve, and the molecular sieve skeleton structure will not collapse and be damaged over a large area during the process, so the obtained molecular sieve has both high micropore volume, adsorption capacity and compressive strength, and exhibits good adsorption selectivity and good mass transfer performance when used for adsorption separation of paraxylene, and is conducive to the long-term operation of the adsorption separation device. At the same time, the adsorbent also has a high basic bulk density, thereby allowing a higher adsorption separation efficiency within a unit adsorbent loading volume.

[0018] Other features and advantages of the present application will be described in detail in the subsequent detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings are used to provide a further understanding of the present application and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present application but do not constitute a limitation to the present application. In the accompanying drawings:

[0020] Figure 1 The pore size distribution curve of adsorbent A prepared in Example 1 of the present application;

[0021] Figure 2 The solid nuclear magnetic resonance of adsorbent A prepared in Example 1 of the present application 29 Si spectrum;

[0022] Figure 3 The solid nuclear magnetic resonance of adsorbent A prepared in Example 1 of the present application 27 Al spectrum;

[0023] Figure 4 The pore size distribution curve of adsorbent B prepared in Example 2 of the present application;

[0024] Figure 5 The pore size distribution curve of the adsorbent E prepared in Comparative Example 1 of the present application;

[0025] Figure 6 The pore size distribution curve of the adsorbent H prepared in Comparative Example 3 of the present application;

[0026] Figure 7 The solid nuclear magnetic resonance of the adsorbent H prepared in Comparative Example 3 of this application 29 Si spectrum;

[0027] Figure 8 The solid nuclear magnetic resonance of the adsorbent H prepared in Comparative Example 3 of this application 27 Al spectrum; and

[0028] Fig. 9Schematic diagram of the small-scale simulated moving bed adsorption separation implemented in Example 5. DETAILED DESCRIPTION

[0029] The specific implementation methods of the present application are described in detail below, but it should be noted that the protection scope of the present application is not limited by these specific implementation methods, but is determined by the claims in the appendix.

[0030] Any specific numerical value disclosed herein (including the endpoint of the numerical range) is not limited to the exact value of the numerical value, but should be understood to also cover values ​​close to the exact value, such as all possible numerical values ​​within the range of ±5% of the exact value. In addition, for the disclosed numerical range, the endpoint values ​​of the range, the endpoint values ​​and the specific point values ​​in the range, and the specific point values ​​can be arbitrarily combined to obtain one or more new numerical ranges, and these new numerical ranges should also be regarded as specifically disclosed herein.

[0031] Unless otherwise specified, the terms used herein have the same meaning as commonly understood by those skilled in the art. If a term is defined herein and its definition is different from the commonly understood meaning in the art, the definition herein shall prevail.

[0032] In the present application, the micropore and mesopore pore volumes, specific surface areas and pore size distributions of molecular sieves are determined by nitrogen physical adsorption method.

[0033] In this application, except for the contents clearly stated, any matters or items not mentioned are directly applicable to the aspects known in the art without any changes. Moreover, any embodiment described herein can be freely combined with one or more other embodiments described herein, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of this application, and should not be regarded as new contents not disclosed or anticipated herein, unless a person skilled in the art considers that the combination is obviously unreasonable.

[0034] All patent and non-patent literature, including but not limited to textbooks and journal articles, mentioned herein are incorporated herein by reference in their entirety.

[0035] As described above, in a first aspect, a method for preparing an adsorbent based on X molecular sieve is provided, comprising the following steps:

[0036] 1) mixing the X molecular sieve with a binder, forming and calcining to obtain a formed body;

[0037] 2) treating the molded body obtained in step 1) with an alkaline solution to in-situ crystallize the binder therein to obtain a crystallized product;

[0038] 3) performing ion exchange on the crystallized product obtained in step 2) with an ammonium salt solution, and calcining the product under a flowing atmosphere to obtain a calcined product; and

[0039] 4) The calcined product obtained in step 3) is subjected to barium ion exchange and optionally potassium ion exchange, and then dried to obtain the adsorbent.

[0040] In the method of the present application, after the X molecular sieve and the binder are mixed, formed and calcined, the binder is subjected to in-situ crystallization treatment to crystallize the binder into the X molecular sieve in-situ, and then the crystallized product (i.e., the molded body treated with the alkaline solution in step 2) is subjected to ammonium salt solution ion exchange and calcined under a flowing atmosphere. During the ion exchange process, part of the Na in the molecular sieve is + Ions are NH4 + Ion exchange substitution, during the calcination process, NH4 in the molecular sieve framework + It will be converted into gaseous ammonia and hydrogen protons. Due to the instability of the H-type molecular sieve skeleton structure with a low silicon-aluminum ratio, the Si-O-Al bond at the corresponding position will be broken, and the molecular sieve skeleton structure will be cut to produce mesoporous channels, and then barium ion exchange or barium and potassium ion exchange will be carried out to obtain BaX or BaKX adsorbents. The resulting adsorbent has mesoporous channels (the most probable pore size is usually in the range of 2.0-8.0nm). In addition, since only partial rupture of Si-O-Al bonds occurs during the formation of mesopores, rather than the collapse of the molecular sieve skeleton structure, the adsorbent has high micropore volume, adsorption capacity and compressive strength. The adsorbent as a whole has good adsorption selectivity and good mass transfer performance. Under the same conditions of adsorption selectivity, the total adsorption capacity and mass transfer rate of paraxylene can be improved, thereby increasing the processing capacity of the device. Higher compressive strength can also guarantee the operation cycle of the adsorption separation device.

[0041] In a preferred embodiment, the mass ratio of the X molecular sieve to the binder in step 1) is 80:20 to 99:1, preferably 95:5 to 99:1.

[0042] In a preferred embodiment, the SiO2 / Al2O3 molar ratio of the X molecular sieve used in step 1) is 2.0-2.6, for example, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5 or 2.6, and the particle size is 0.8-2.5 μm, for example, 0.8 μm, 0.9 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.4 μm or 2.5 μm. Further preferably, the SiO2 / Al2O3 molar ratio of the X molecular sieve used is 2.1-2.4, and the particle size is 0.8-1.5 μm.

[0043] In a preferred embodiment, the binder used in step 1) is selected from kaolinite, dickite, perlite, refractory stone, halloysite, hydromica, montmorillonite, or a combination thereof. Further preferably, the binder used contains 75-95% by mass of kaolinite and 5-15% by mass of halloysite. The binder with such composition can be better transformed into X molecular sieve during the in-situ crystallization in step 2), thereby improving the adsorption capacity and separation performance of the adsorbent.

[0044] In a preferred embodiment, the calcination temperature in step 1) is 500-700°C, for example, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C or 700°C; the calcination time is 0.5-6.0h, for example, 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h or 6.0h.

[0045] According to the present application, the molding described in step 1) can be achieved by various molding methods commonly used in the art, and the present application has no strict restrictions on this. In certain preferred embodiments, the molding described in step 1) is rolling ball molding, and the resulting molded body is in the form of a sphere. In particular, the rolling ball molding includes gradually aggregating and growing the molding powder obtained by mixing the X molecular sieve and the binder in a rolling plate, and continuously spraying water during rolling to wet the surface of the sphere and adhere the powder.

[0046] According to the present application, in step 2), the molded body after molding and calcination is treated with an alkaline solution to make the binder in the molded body crystallize in situ and transform into X molecular sieve, thereby increasing the content of active components in the molded body. In a preferred embodiment, the alkaline solution used in step 2) is a mixed solution of sodium hydroxide and water glass, wherein the concentration of sodium hydroxide is 1.2-4.0 mol / L, such as 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L, 2.4 mol / L, 2.8 mol / L, 3.2 mol / L, 3.6 mol / L or 4.0 mol / L, preferably 1.2-2.0 mol / L, and the concentration of silicon dioxide is 6-20 g / L, such as 6 g / L, 8 g / L, 10 g / L, 12 g / L, 14 g / L, 16 g / L, 18 g / L or 20 g / L, preferably 10-15 g / L.

[0047] In a preferred embodiment, the liquid-to-solid volume ratio of the alkaline solution to the molded body in the alkaline solution treatment in step 2) is 1.2-3.0:1, for example, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2.0:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1 or 3.0:1, preferably 2.0-3.0:1.

[0048] In a preferred embodiment, the conditions of the alkaline solution treatment in step 2) include: a treatment temperature of 90-100°C, for example, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C, and a treatment time of 1.5-6.0h, for example, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h or 6.0h.

[0049] In the above preferred embodiments, step 2) can better achieve the transformation of the binder into X molecular sieve, thereby improving the adsorption capacity and separation performance of the obtained adsorbent.

[0050] According to the present application, in step 3), NH4 + The ions are partially exchanged to the cation exchangeable sites of the X molecular sieve in the crystallized product. In a preferred embodiment, in step 3), the ammonium salt is selected from ammonium chloride, ammonium sulfate, ammonium nitrate, or a combination thereof.

[0051] In a preferred embodiment, in step 3), the concentration of the ammonium salt solution is 0.2-5.0 mol / L, for example, 0.2 mol / L, 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L, 3.5 mol / L, 4.0 mol / L, 4.5 mol / L or 5.0 mol / L, preferably 0.2-2.0 mol / L.

[0052] In a preferred embodiment, in step 3), the liquid-to-solid volume ratio of the ammonium salt solution to the crystallized product during the ion exchange process is 2-10:1, for example, 2:1, 4:1, 6:1, 8:1 or 10:1, preferably 2-5:1.

[0053] In a preferred embodiment, in step 3), the ion exchange conditions include: a temperature of 25-95°C, for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, preferably 25-55°C, and a time of 0.5-5.0h, for example, 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h or 5.0h, preferably 0.5-2.0h.

[0054] According to the present application, in step 3), the purpose of calcining under a flowing atmosphere is to selectively destroy the skeleton structure of the molecular sieve, thereby forming mesoporous channels, while avoiding significant damage to the microporous channels of the molecular sieve. In a preferred embodiment, in step 3), the calcining temperature is 100-500°C, for example, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C or 500°C, preferably 150-350°C; the calcining time is 0.5-6.0h, for example, 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h or 6.0h, preferably 1.0-6.0h, more preferably 1.0-2.0h.

[0055] In a preferred embodiment, in step 3), the flowing atmosphere is a flowing air atmosphere or an inert flowing atmosphere (such as a flowing nitrogen atmosphere), more preferably a flowing air atmosphere.

[0056] In a preferred embodiment, in step 3), the gas flow rate of the flowing atmosphere is 5-20 L / h, for example, 5 L / h, 7 L / h, 9 L / h, 11 L / h, 13 L / h, 15 L / h, 17 L / h, 19 L / h or 20 L / h, preferably 15-20 L / h.

[0057] In the above preferred embodiments, the calcination treatment in step 3) can better avoid significant damage to the molecular sieve framework structure, thereby forming mesoporous channels while allowing the resulting adsorbent to have higher micropore volume, adsorption capacity and separation performance.

[0058] According to the present application, in step 4), the calcined product obtained in step 3) is subjected to cation exchange, so that at least part of the cation positions of the X molecular sieve contained therein are replaced by Ba 2+ and / or K + Ion occupation. Preferably, the cations (Ba 2+ and / or K + ) and the total number of moles of Na in the molecular sieve +The ratio of the molar numbers of ions, that is, the exchange ratio, is 1.5-3.0:1.

[0059] Without being limited to a specific theory, it is believed that the cation exchange treatment in step 4) can coordinate barium ions or barium ions and potassium ions with oxygen ions in the X molecular sieve framework, so that a high PX selective adsorption force field with a symmetry of the D2 group is generated in the X molecular sieve supercage, so that the resulting adsorbent has higher separation performance.

[0060] In certain preferred embodiments, only barium ion exchange is performed in step 4), and the barium ion exchange is performed using a solution of a soluble barium salt, wherein the soluble barium salt is preferably selected from barium chloride, barium nitrate, or a combination thereof.

[0061] In other preferred embodiments, in step 4), barium ion exchange is performed first and then potassium ion exchange, or potassium ion exchange is performed first and then barium ion exchange, and the barium ion exchange is performed using a solution of a soluble barium salt, and the soluble barium salt is preferably selected from barium chloride, barium nitrate, or a combination thereof; the potassium ion exchange is performed using a potassium salt solution, and the potassium salt is preferably selected from potassium chloride, potassium nitrate, or a combination thereof.

[0062] In other preferred embodiments, in step 4), the barium ion and potassium ion exchange are simultaneously carried out using a mixed solution containing a soluble barium salt and a potassium salt, and the soluble barium salt and the potassium salt are selected as described above.

[0063] In a preferred embodiment, the conditions for the barium ion exchange and optional potassium ion exchange in step 4) include: a temperature of 30-95°C, such as 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, preferably 80-95°C, and a time of 2.0-48.0h, such as 2.0h, 6.0h, 10.0h, 14.0h, 18.0h, 22.0h, 26.0h, 30.0h, h, 34.0h, 38.0h, 42.0h, 46.0h, 48.0h, preferably 12.0-36.0h. Further preferably, the volume space velocity of the barium salt solution, potassium salt solution and barium salt potassium salt mixed solution in the ion exchange in step 4) is independently 1.0-20.0h -1 , for example 1.0h -1 , 2.0h -1 , 3.0h -1 , 4.0h -1 , 5.0h -1 , 6.0h -1 , 7.0h -1 , 8.0h -1 , 9.0h -1 , 10.0h-1 , 12.0h -1 , 14.0h -1 , 16.0h -1 , 18.0h -1 or 20.0h -1 , preferably 1.0-10.0h -1 .

[0064] According to the present application, the product after ion exchange in step 4) is dried to obtain the X molecular sieve-based adsorbent, and the drying temperature is preferably 100-120° C. and the drying time is preferably 6.0-24.0 h.

[0065] In certain specific embodiments, the adsorbent preparation method of the present application comprises the following steps:

[0066] 1) Mixing the X molecular sieve and the binder evenly to obtain a molding powder, wherein the binder content is 1-8% by mass and the X molecular sieve content is 99-92% by mass, placing the molding powder on a rolling molding device, and rolling while spraying water until the powder is completely aggregated into small balls, drying the formed small balls, and then calcining at 500-700° C.;

[0067] 2) treating the pellets formed and calcined in step 1) with an alkaline solution to in-situ crystallize the binder therein;

[0068] 3) exchanging the pellets obtained by in-situ crystallization in step 2) with an ammonium salt solution for 0.5-5.0 hours, and calcining the pellets under a flowing air atmosphere; and

[0069] 4) exchanging the beads obtained in step 3) with barium ions or barium potassium ions, and then drying them to obtain the adsorbent.

[0070] In the second aspect, the present application provides an adsorbent based on X molecular sieve, comprising 98.0-99.0 mass% of X molecular sieve and 1.0-2.0 mass% of matrix, and the micropore volume is 0.18-0.30mL / g, preferably 0.24-0.30mL / g, the mesopore volume is 0.01-0.1mL / g, preferably 0.01-0.05mL / g, the most probable pore size of the mesopore is 2.0-8.0nm, preferably 2.0-5.0nm, the 250N compressive crushing rate is less than 5.5%, and the basic bulk density is 0.91-1.20g / cm 3 .

[0071] According to the present application, the matrix may be a binder, for example, may be selected from kaolinite, dickite, perlite, refractory stone, halloysite, hydromica, montmorillonite, or a combination thereof.

[0072] In a preferred embodiment, the 250N compression crushing rate of the adsorbent is less than 5.3%, such as less than 5.0%, less than 4.0% or less than 3.0%, and the bulk density is 0.92-1.20 g / cm 3 , for example 0.95 g / cm 3 、0.98g / cm 3 , 1.01g / cm 3 , 1.04g / cm 3 , 1.07g / cm 3 , 1.10g / cm 3 , 1.13g / cm 3 , 1.16g / cm 3 , 1.19g / cm 3 or 1.20g / cm 3 The adsorbent of the present application has a low compression crushing rate, indicating that it has a high compressive strength, which is conducive to the long-term operation of the adsorption separation device. At the same time, the adsorbent also has a high basic bulk density, thereby allowing a higher adsorption separation efficiency within a unit adsorbent loading volume.

[0073] In a preferred embodiment, at least part of the cationic sites of the X molecular sieve contained in the adsorbent are occupied by barium and / or potassium ions, and the Ba content in the adsorbent calculated as BaO is 38.0-41.0 mass%, for example, 38.0 mass%, 38.5 mass%, 39.0 mass%, 39.5 mass%, 40.0 mass%, 40.5 mass% or 41.0 mass%, based on the weight of the adsorbent, and the K content calculated as KO is 0-3.0 mass%, for example, 0.5 mass%, 1.0 mass%, 1.5 mass%, 2.0 mass%, 2.5 mass% or 3.0 mass%.

[0074] In a preferred embodiment, by 29 Si and 27According to the measurement of Al high-resolution magic angle nuclear magnetic resonance, the relative content of the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structural tetrahedrons in the framework structure of the adsorbent is not less than 60 mol%, for example, 60-85 mol%, such as 60 mol%, 70 mol%, 80 mol% or 85 mol%, and the relative content of non-framework aluminum in the total aluminum species is not higher than 5 mol%, for example, 1-5 mol%, such as 1.0 mol%, 1.5 mol%, 2.0 mol%, 2.5 mol%, 3.0 mol%, 3.5 mol%, 4.0 mol%, 4.5 mol% or 5.0 mol%. Further preferably, the relative content of the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structural tetrahedrons in the framework structure of the adsorbent is not less than 70 mol%, for example, 70-85 mol%, and the relative content of non-framework aluminum in the total aluminum species is not higher than 3 mol%, for example, 1-3 mol%.

[0075] In a preferred embodiment, the micropore specific surface area of ​​the adsorbent is 400-650m 2 / g, external specific surface area is 1-30m 2 / g, and the corresponding particle size when the cumulative particle size distribution number reaches 50% is 425-600μm.

[0076] In a particularly preferred embodiment, the X molecular sieve-based adsorbent is prepared by the method described in the first aspect of the present application.

[0077] In a third aspect, there is provided the use of the X molecular sieve-based adsorbent of the present application for the adsorptive separation of p-xylene, in particular, the use of separating p-xylene from mixed C8 aromatics containing p-xylene by adsorption.

[0078] The adsorbent of the present application and the adsorbent prepared by the method of the present application are particularly suitable for the liquid phase adsorption separation process of aromatic isomers, especially the adsorption separation of p-xylene from mixed C8 aromatics, such as a mixture of o-xylene, m-xylene, p-xylene and ethylbenzene.

[0079] In a fourth aspect, the present application provides a method for adsorbing and separating paraxylene from mixed C8 aromatics containing paraxylene by liquid phase adsorption separation, comprising the steps of contacting the mixed C8 aromatics with the adsorbent of the present application or the adsorbent prepared by the method of the present application to adsorb paraxylene, and contacting the adsorbent after adsorbing paraxylene with a desorbent to desorb the paraxylene.

[0080] In a preferred embodiment, the liquid phase adsorption separation can be carried out by connecting multiple columns in series, or by using a simulated moving bed realized by a rotary valve or a solenoid valve group.

[0081] In a preferred embodiment, the desorbent is selected from p-diethylbenzene, toluene, or a combination thereof.

[0082] In a preferred embodiment, the operating pressure of the adsorption separation is 0.3-1.5 MPa, for example, 0.3 MPa, 0.5 MPa, 0.8 MPa, 1.0 MPa, 1.2 MPa, 1.4 MPa or 1.5 MPa, and the operating temperature is 120-190°C, for example, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C or 190°C.

[0083] Example

[0084] The present application is further described below by way of examples, but the present application is not limited thereto.

[0085] In the following examples and comparative examples:

[0086] The total pore volume, micropore volume, mesopore volume, specific surface area and pore size distribution of the adsorbent were determined by nitrogen physical adsorption method. The test instrument was ASAP 2020 physical adsorption instrument from Micromeritics, USA. Before the test, the samples were heated at 300-450℃ and vacuum (<10 -2 The molecular sieve was degassed at 77 K for 6.0-16.0 h under 400 ° C (370 ° C), preferably at 300 ° C for 10.0 h. Nitrogen physical adsorption was carried out at 77 K. The total specific surface area and average adsorption pore size of the molecular sieve were calculated by the BET (Brunauer-Emmett-Teller) equation; P0 was 0.1 MPa, and the total pore volume of the sample was determined by the adsorption amount of nitrogen when the relative adsorption amount P / P0 = 0.975. The micropore specific surface area, external specific surface area and micropore volume were calculated using the t-plot method, and the mesopore pore size distribution was calculated using the BJH method (Barrett-Joyner-Halenda).

[0087] The elemental chemical composition of the adsorbent was characterized by X-ray fluorescence spectrometry (XRF), using a Shimadzu XRF-1800 X-ray fluorescence spectrometer. The qualitative analysis of BaO, K2O and Na2O was performed based on the corresponding relationship between the wavelength of characteristic X-ray fluorescence and the atomic number, and the quantitative analysis of BaO, K2O and Na2O was performed based on the comparison of the peak intensity at the wavelength of X-ray fluorescence and the standard sample.

[0088] Coordination number and existence form of silicon and aluminum atoms in adsorbents 29 Si and 27 Al high resolution magic angle nuclear magnetic resonance (MAS NMR) characterization, 29 Si core and 27The single pulse spectra of Al nuclei were completed using a Bruker Avance III 500WB spectrometer. 29 Si core and 27 The resonant frequencies of the Al nucleus are 500.1MHz and 89.6MHz respectively. The relative content of the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in the adsorbent skeleton structure to the total silicon species is 29 The ratio of the sum of the peak areas corresponding to the chemical shifts -86 and -90 ppm in the Si MAS NMR spectrum to the sum of all the peak areas corresponding to the chemical shifts -70 to -120 ppm; the relative content of non-framework aluminum to total aluminum species is 27 The ratio of the peak area corresponding to 0 ppm in the Al MAS NMR spectrum to the sum of all peak areas corresponding to -20 to 100 ppm

[0089] The adsorption capacity of the adsorbent is determined by contacting nitrogen gas carrying toluene (toluene partial pressure is 0.5 MPa) with a certain mass of adsorbent at 35°C until toluene reaches adsorption equilibrium. The adsorption capacity of the adsorbent material is calculated based on the mass difference of the adsorbent before and after toluene adsorption.

[0090] The adsorption selectivity of the adsorbent material was determined using a dynamic pulse test device: the device consists of a feed system, an adsorption column, a heating furnace, a pressure control valve, etc. The adsorption column is a Ф6×1800mm stainless steel tube, and the adsorption material loading is 50 ml. The lower inlet of the adsorption column is connected to the feed and nitrogen system, and the upper outlet is connected to the pressure control valve, and then connected to the effluent collector. The desorbent used in the experiment is 30 volume % of p-diethylbenzene (PDEB) and 70 volume % of n-heptane. The pulse feed liquid is composed of 5 volume % of ethylbenzene (EB), p-xylene (PX), m-xylene (MX), o-xylene (OX), n-nonane (NC9) and 75 volume % of p-diethylbenzene.

[0091] The method for determining the adsorption selectivity of the adsorbent material is as follows: weigh the adsorbent material particles with a particle size of 300-850μm and place them into the adsorption column for compaction, dehydrate and activate them at 160-190℃ in a nitrogen atmosphere, and then introduce a desorbent to remove the gas in the system. Raise the system pressure to 0.8MPa and the temperature to 177℃, stop introducing the desorbent, and wait for 1.0h. -18 ml of pulse feed liquid was introduced at a volumetric space velocity, and then the desorbent was introduced at the same volumetric space velocity. Three drops of desorbent sample were taken every 2 minutes and analyzed by gas chromatography. The desorption curves of the above components were plotted with the volume of desorbent used for desorption as the horizontal coordinate and the concentrations of NC9, EB, PX, MX and OX as the vertical coordinate. Among them, NC9 is not adsorbed and can be used as a tracer to obtain the dead volume of the adsorption system. The midpoint of the half-peak width of the tracer is taken as the zero point, and the net retention volume R from the midpoint of the half-peak width of the components EB, PX, MX, and OX to the zero point is measured. The net retention volume of any component is proportional to the distribution coefficient at adsorption equilibrium, which reflects the interaction between each component and the adsorbent material. The ratio of the net retention volumes of the two components is the selectivity β. For example, the ratio of the net retention volume of PX to the net retention volume of EB is the ratio of the adsorption performance of the adsorbent for PX and EB, that is, the adsorption selectivity of the adsorbent for PX relative to EB, recorded as β P / E Similarly, the adsorption selectivity of the adsorbent material for PX relative to MX and OX is denoted as β P / M and β P / O The volume of desorbent required when the MX concentration in the effluent increases from 10% to 90% at the front edge of the pulse desorption curve of MX is defined as the adsorption rate [S A ] 10-90 The desorption rate [S D ] 90-10 ,[S A ] 10-90 With [S D ] 90-10 The smaller the value, the higher the mass transfer performance of the adsorption material.

[0092] The relative content of active component and matrix of adsorbent is determined by measuring the toluene adsorption of adsorbent and X zeolite of the same mass respectively. The ratio of the two is the content of active component (X molecular sieve), and 1-active component percentage is the matrix content.

[0093] The particle size of the adsorbent is determined by laser diffraction using a Masterizer-2000 X-ray fluorescence spectrometer from the British company MALVERN. The particle size distribution of the sample is obtained based on the difference in laser scattering angles for different particle sizes. The particle size (D50) corresponding to 50% of the cumulative particle size distribution of a sample is taken as the average particle size of the sample.

[0094] The compressive strength of the adsorbent is represented by the crushing rate of the small ball adsorbent under 250N. The lower the crushing rate, the higher the compressive strength. The determination method is: after the adsorbent beads pass through a 300μm sieve, take the adsorbent beads with a particle size greater than 300μm, put about 1.5mL into a stainless steel cylinder and weigh it. During the determination, install a pin that has an interference fit with the stainless steel cylinder, press once under a pressure of 250N, pour out the adsorbent, pass through a 300μm sieve again, take the adsorbent beads with a particle size greater than 300μm and weigh them. The ratio of the reduction in the adsorbent with a particle size greater than 300μm before and after compression to the adsorbent with a particle size greater than 300μm before compression is the crushing rate of the adsorbent.

[0095] In the following examples and comparative examples, unless otherwise specified, all reagents and raw materials used are commercially available products.

[0096] Example 1

[0097] Adsorbent preparation:

[0098] (1) 92 kg (basic weight, the same below) of X molecular sieve (SiO2 / Al2O3 molar ratio of 2.35, particle size of 1.0 μm, Na mass fraction of 16.7% based on Na2O) and 8 kg of binder (containing 90% by mass of kaolinite and 10% by mass of halloysite) were mixed evenly, put into a rotating disk, and sprayed with an appropriate amount of deionized water while rolling to make the solid powder aggregate into small balls. The amount of water sprayed during rolling was 8% by mass of the solid powder. After screening, small balls with a particle size of 300-1000 μm were taken, dried at 80°C for 10.0 h, and calcined at 540°C for 4.0 h to obtain adsorbent matrix small balls.

[0099] (2) The pellets calcined in step 1) were subjected to in-situ crystallization treatment using a mixed solution of sodium hydroxide and water glass, wherein the sodium hydroxide concentration in the mixed solution was 1.5 mol / L, the silicon dioxide concentration was 12 g / L, and the liquid-to-solid volume ratio was 3.0:1. After treatment at 95°C for 4.0 h, the pellets were washed with deionized water until the pH value was less than 8.0, and dried at 100°C for 8.0 h.

[0100] (3) treating the pellets dried in step 2) with a 0.8 mol / L ammonium chloride solution at a liquid-to-solid volume ratio of 5.0:1 at 40°C for 1.0 h, washing with deionized water, drying at 120°C for 10.0 h, and finally calcining at 200°C for 2.0 h.

[0101] (4) 130 ml of the pellets obtained after calcination in step 3) were placed in an ion exchange column for cation exchange, and a mixed solution of 0.18 mol / L barium nitrate and 0.07 mol / L potassium nitrate was used for 8.0 h. -1The exchange was continued for 6.0 h at a volume space velocity of 0.1 MPa and 94°C, and the total amount of the mixed solution was 5000 mL. After the ion exchange was completed, the solid was washed with 700 mL of deionized water at 70°C, purged with a nitrogen atmosphere at 70°C for 24.0 h, and dried at 100°C for 8.0 h to obtain adsorbent A.

[0102] The Ba mass content of the obtained adsorbent A is 40.70% as BaO, and the K mass content is 0.61% as K2O. Through nitrogen physical adsorption measurement, the micropore volume of adsorbent A is 0.277mL / g, the mesopore volume is 0.032mL / g, the mesopore most probable pore diameter is 3.2nm, the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in the framework structure accounts for 75mol% of the total silicon species, and the non-framework aluminum accounts for 2.6mol% of the total aluminum species. Its pore size distribution curve is shown in Figure 1. Figure 1 , solid-state NMR 29 Si spectrum is shown in Figure 2 , solid-state NMR 27 Al spectrum is shown in Figure 3 The composition and properties of adsorbent A are shown in Table 1.

[0103] Adsorbent performance test

[0104] 1.0 g and 50 mL of adsorbent A were taken for toluene gas phase adsorption experiment to determine its adsorption capacity and liquid phase pulse experiment to determine its adsorption selectivity as well as adsorption and desorption rates, respectively. The results are shown in Table 2.

[0105] Example 2

[0106] Adsorbent B was prepared by referring to the method of Example 1, except that the concentration of the ammonium chloride solution in step (3) was 0.2 mol / L.

[0107] The Ba mass content of the obtained adsorbent B is 41.00% as BaO, the K mass content is 0.57% as K2O, the micropore volume is 0.282mL / g, the mesopore volume is 0.030mL / g, the mesopore most probable pore diameter is 3.0nm, the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 74mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 1.8mol% of the total aluminum species. Its pore size distribution curve is as follows: Figure 4 The composition and properties of adsorbent B are shown in Table 1.

[0108] The adsorbent performance test was carried out with reference to Example 1. The test results are shown in Table 2.

[0109] Example 3

[0110] Adsorbent C was prepared by referring to the method of Example 1, except that the concentration of the ammonium chloride solution in step 3) was 2.0 mol / L, the calcination temperature was 500° C., and the calcination time was 1.0 h.

[0111] The Ba mass content of the obtained adsorbent C is 38.90% as BaO, the K mass content is 0.59% as K2O, the micropore volume is 0.248mL / g, the mesopore volume is 0.033mL / g, the mesopore most probable pore diameter is 3.4nm, the sum of the Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 65mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 3.9mol% of the total aluminum species. The composition and properties of adsorbent C are shown in Table 1.

[0112] The adsorbent performance test was carried out with reference to Example 1. The test results are shown in Table 2.

[0113] Example 4

[0114] Adsorbent D was prepared by referring to the method of Example 1, except that in step 3), the temperature of the ammonium chloride solution treatment was 55° C., the calcination temperature was 500° C., and the calcination time was 1.0 h.

[0115] The Ba mass content of the obtained adsorbent D is 38.90% as BaO, the K mass content is 0.59% as K2O, the micropore volume is 0.249mL / g, the mesopore volume is 0.042mL / g, and the mesopore most probable pore diameter is 3.1nm. The sum of the tetrahedrons of Si(OAl)4 and Si(OSi)1(OAl)3 structures in its framework structure accounts for 71mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 2.6mol% of the total aluminum species. The composition and properties of adsorbent D are shown in Table 1.

[0116] The adsorbent performance test was carried out with reference to Example 1. The test results are shown in Table 2.

[0117] Example 5

[0118] Adsorbent E was prepared by referring to the method of Example 1, except that the solution used for cation exchange in step 4) was 0.18 mol / L barium nitrate.

[0119] The Ba mass content of the obtained adsorbent E is 41.3% as BaO, and it does not contain K element. The micropore volume is 0.271mL / g, the mesopore volume is 0.028mL / g, and the mesopore most probable pore diameter is 2.9nm. The sum of the Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 76mol% of the total silicon species, and the non-framework aluminum accounts for 2.5mol% of the total aluminum species. The composition and properties of adsorbent E are shown in Table 1.

[0120] The adsorbent performance test was carried out with reference to Example 1. The test results are shown in Table 2.

[0121] Comparative Example 1

[0122] Take 10.9 kg of sodium aluminate solution (containing 17.3 mass % of Al2O3 and 21.0 mass % of Na2O), 48.3 kg of deionized water and 13.1 kg of sodium hydroxide, stir to completely dissolve the solid alkali, then add 66.8 kg of water glass (containing 28.3 mass % of SiO2 and 8.8 mass % of Na2O), stir until uniform, and age at 25°C for 20.0 h to obtain a directing agent, wherein the molar ratio of each material is: SiO2 / Al2O3=17, Na2O / SiO2=0.95, H2O / SiO2=17.6.

[0123] Take 174 kg of water glass, 768 kg of deionized water, and 13 kg of sodium hydroxide, stir them thoroughly at 25 ° C, add 178 kg of sodium aluminate and mix them well, then add 0.8 kg of directing agent, stir evenly, add 9.5 kg of dimethyl hexadecyl [3-(trimethoxysilyl)propyl] ammonium chloride [(CH3O)3Si(CH2)3N(CH3)2(CH2) with a concentration of 60 mass% 15 CH3Cl] aqueous solution is used as the template (R) solution, and stirring is continued until the mixture is uniform to obtain a synthetic system, wherein the molar ratio of each material is: SiO2 / Al2O3=2.8, Na2O / SiO2=1.23, H2O / SiO2=65, the mass ratio of R / SiO2 is 0.06, and the amount of the directing agent added is calculated as 0.2% of the mass of SiO2 in the synthetic system based on the SiO2 therein.

[0124] The above synthesis system was heated to 100°C and hydrothermally crystallized for 8.0 hours under static conditions. The crystallized product was washed with deionized water until the pH value of the washing solution was less than 10, and the obtained solid was dried at 80°C for 12.0 hours, and calcined at 200°C for 1.0 hour, 380°C for 1.0 hour, and 540°C for 4.0 hours in an air atmosphere to obtain a mesoporous NaX molecular sieve.

[0125] 92kg (basic weight, the same below) of the above mesoporous X molecular sieve (SiO2 / Al2O3 molar ratio of 2.35, particle size of 1.0μm, Na mass fraction of 16.7% in terms of Na2O, mesoporous pore volume of 0.027mL / g) and 8kg of binder (containing 90% by mass of kaolinite and 10% by mass of halloysite) were mixed evenly, put into a turntable, and an appropriate amount of deionized water was sprayed while rolling to make the solid powder aggregate into small balls. The amount of water sprayed during rolling was 8% by mass of the solid powder. After screening, small balls with a particle size of 300-850μm were taken, dried at 80°C for 10.0h, and calcined at 540°C for 4.0h to obtain adsorbent matrix small balls.

[0126] The calcined pellets were subjected to in-situ crystallization treatment using a mixed solution of sodium hydroxide and water glass, wherein the sodium hydroxide concentration in the mixed solution was 1.5 mol / L, the water glass concentration was 12 g / L, and the liquid-to-solid volume ratio was 3.0: 1. After treatment at 95°C for 4.0 h, the pellets were washed with deionized water until the pH value was less than 8.0, and dried at 100°C for 8.0 h.

[0127] 130 mL of the pellet obtained after in-situ crystallization was placed in an ion exchange column for cation exchange. A mixed solution of 0.18 mol / L barium nitrate and 0.07 mol / L potassium nitrate was used for 8.0 h. -1 The exchange was continued for 6.0 h at a volume space velocity of 0.1 MPa and 94°C, and the total amount of the mixed solution was 5000 mL. After the ion exchange was completed, the solid was washed with 700 mL of deionized water at 70°C, purged with a nitrogen atmosphere at 70°C for 24.0 h, and dried at 100°C for 8.0 h to obtain adsorbent F.

[0128] The Ba mass content of the obtained adsorbent F is 39.10% as BaO, the K mass content is 0.60% as K2O, the micropore volume is 0.238 mL / g, the mesopore volume is 0.009 mL / g, and the pore size distribution curve is as follows: Figure 5 As shown, no obvious mesoporous distribution peak is observed. The sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 82 mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 0.9 mol% of the total aluminum species. The composition and properties of adsorbent F are shown in Table 1.

[0129] The adsorbent performance test was carried out with reference to Example 1. The test results are shown in Table 2.

[0130] Comparative Example 2

[0131] Adsorbent G was prepared by referring to the method of Example 1, except that in step 3), calcination was performed directly instead of ammonium chloride solution treatment.

[0132] The Ba mass content of the obtained adsorbent G is 40.80% in terms of BaO, the K mass content is 0.59% in terms of K2O, the micropore volume is 0.249mL / g, the mesopore volume is 0.011mL / g, and its pore size distribution curve does not show an obvious mesopore distribution peak, indicating that the measured amount of mesopore channels with regular pore sizes does not exist in the adsorbent G, and a small amount of mesopore volume may only be caused by irregular pores formed by crystal accumulation. The sum of Si(OAl)4 and Si(OSi)1(OAl)3 structural tetrahedrons in its framework structure accounts for 79mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 1.1mol% of the total aluminum species. The composition and properties of adsorbent G are shown in Table 1.

[0133] The adsorbent performance test was carried out with reference to Example 1. The test results are shown in Table 2.

[0134] Comparative Example 3

[0135] Adsorbent H was prepared according to the method of Example 3, except that the concentration of the ammonium chloride solution in step 3) was 10.0 mol / L.

[0136] The Ba mass content of the obtained adsorbent H is 33.50% as BaO, the K mass content is 0.43% as K2O, the micropore volume is 0.142mL / g, the mesopore volume is 0.089mL / g, and the mesopore most probable pore diameter is 4.8nm. The sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 56mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 7.8mol% of the total aluminum species.

[0137] The pore size distribution curve of adsorbent H is shown in Figure 6 , solid-state NMR 29 Si spectrum is shown in Figure 7 , solid-state NMR 27 Al spectrum is shown in Figure 8 The composition and properties of adsorbent H are shown in Table 1.

[0138] The adsorbent performance test was carried out with reference to Example 1. The test results are shown in Table 2.

[0139] Comparative Example 4

[0140] The in-situ crystallized beads were prepared by referring to steps (1) and (2) of Example 1. 130 ml of the beads were placed in an ion exchange column for cation exchange. A mixed solution of 0.18 mol / L barium nitrate, 0.07 mol / L potassium nitrate and 0.8 mol / L ammonium chloride was used for 8.0 h. -1The exchange was continued for 6.0 h at a volume space velocity of 0.1 MPa and 94°C, and the total amount of the mixed solution was 5000 mL. After the ion exchange was completed, the solid was washed with 700 mL of deionized water at 70°C, purged with a nitrogen atmosphere at 70°C for 24.0 h, dried at 120°C for 1.0 h, and then calcined at 500°C for 1.0 h to obtain adsorbent I.

[0141] The Ba mass content of the obtained adsorbent I is 35.5% in terms of BaO, the K mass content is 0.95% in terms of K2O, the micropore volume is 0.265mL / g, the mesopore volume is 0.008mL / g, and its pore size distribution curve does not show an obvious mesopore distribution peak, indicating that the measured amount of mesopore channels with regular pore sizes does not exist in the adsorbent I, and the small amount of mesopore volume may only be caused by irregular pores formed by crystal accumulation. The sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 67mol% of the total silicon species, and the relative content of non-framework aluminum accounts for 3.2mol% of the total aluminum species. The composition and properties of adsorbent I are shown in Table 1.

[0142] The adsorbent performance test was carried out with reference to Example 1. The test results are shown in Table 2.

[0143] Comparative Example 5

[0144] Adsorbent J was prepared by referring to the method of Example 1, except that in the ammonium chloride solution treatment step 3), drying was performed at 80° C. for 10.0 h without calcination.

[0145] The Ba mass content of the obtained adsorbent J is 38.60% as BaO, the K mass content is 0.60% as K2O, the micropore volume is 0.261mL / g, the mesopore volume is 0.028mL / g, and the mesopore most probable pore diameter is 3.4nm. The sum of the Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in its framework structure accounts for 63.1mol% of the total silicon species, and the non-framework aluminum accounts for 2.8mol% of the total aluminum species. The composition and properties of adsorbent J are shown in Table 1.

[0146] The adsorbent performance test was carried out with reference to Example 1. The test results are shown in Table 2.

[0147] Table 1 Composition and properties of the adsorbents obtained in each embodiment and comparative example

[0148]

[0149]

[0150] Table 1 (Continued) Composition and properties of the adsorbents obtained in various examples and comparative examples

[0151]

[0152] Table 2 Test results of the adsorbents obtained in each embodiment and comparative example

[0153]

[0154] As shown in Table 1 and Table 2, compared with the adsorbents of Comparative Examples 1-4, the adsorbent of the present application has a higher active component X molecular sieve content, compressive strength, calcined bulk density and adsorption capacity, and exhibits better C8 aromatic hydrocarbon adsorption selectivity and mass transfer performance; compared with the adsorbent of Comparative Example 5, the adsorbent of the present application has significantly higher compressive strength and calcined bulk density.

[0155] Example 6

[0156] The adsorbent A was used to separate p-xylene in a small simulated moving bed with continuous countercurrent flow.

[0157] The small simulated moving bed device comprises 24 adsorption columns connected in series, each column is 195 mm long, the inner diameter of the column is 30 mm, and the total loading amount of the adsorbent is 3300 mL. The ends of the 24 columns connected in series are connected by a circulation pump to form a closed loop, such as Fig. 9 As shown. The four inlet and outlet materials of adsorption raw material, desorbent, extract and raffinate divide the 24 adsorption columns into four sections, namely, the 7 adsorption columns between the adsorption raw material (column 15) and the raffinate (column 21) are the adsorption zone, the 9 adsorption columns between the extract (column 6) and the adsorption raw material (column 14) are the purification zone, the 5 adsorption columns between the desorbent (column 1) and the extract (column 5) are the desorption zone, and the 3 adsorption columns between the raffinate (column 22) and the desorbent (column 24) are the buffer zone. The temperature of the whole adsorption system is controlled at 177°C and the pressure is 0.8MPa.

[0158] During the operation, the desorbent p-diethylbenzene and the raw material were continuously injected into the simulated moving bed at a flow rate of 1420 mL / h and 1310 mL / h, respectively, and the extract and the residual liquid were extracted from the device at a flow rate of 734 mL / h and 1996 mL / h, respectively. The raw material composition is: 9.3% by mass of ethylbenzene, 18.5% by mass of p-xylene, 45.5% by mass of m-xylene, 17.4% by mass of o-xylene, and 9.4% by mass of non-aromatic components.

[0159] Set the circulation pump flow rate to 3720mL / h, and every 70 seconds, four streams of material move simultaneously in the same direction as the liquid flow, and one adsorption column ( Fig. 9In the stable operation state, the purity of p-xylene obtained by adsorbent A is 99.70% by mass, and the yield is 98.55% by mass. After the device is continuously operated for 300 hours, the purity of p-xylene obtained is 99.76% by mass, and the yield is 98.45% by mass.

[0160] Example 7

[0161] Adsorbent B was loaded on a small simulated moving bed apparatus, and an adsorption separation experiment of p-xylene was carried out according to the method of Example 6. The purity of p-xylene obtained under stable operation was 99.73% by mass, and the yield was 98.67% by mass.

[0162] Comparative Example 6

[0163] Comparative adsorbent F was loaded on a small simulated moving bed apparatus, and an adsorption separation experiment of p-xylene was carried out according to the method of Example 6. The purity of p-xylene obtained under stable operation was 97.15% by mass, and the yield was 94.51% by mass.

[0164] Comparative Example 7

[0165] Comparative adsorbent J was loaded on a small simulated moving bed apparatus, and an adsorption separation experiment of p-xylene was carried out according to the method of Example 6. The purity of p-xylene obtained under stable operation was 99.15% by mass, and the yield was 97.81% by mass. After the apparatus had been running continuously for 300 hours, the purity of p-xylene obtained was 97.59% by mass, and the yield was 95.26% by mass.

[0166] By comparing the results of Example 6-7 and Comparative Example 6-7, it can be seen that the use of the adsorbent of the present application in a simulated moving bed device can obtain a high-purity p-xylene product, a high p-xylene product yield per unit time, and can ensure long-term operation of the adsorption separation device.

[0167] The preferred embodiments of the present application are described in detail above; however, the present application is not limited to the specific details in the above embodiments. Within the technical concept of the present application, a variety of simple modifications can be made to the technical solution of the present application, and these simple modifications all fall within the protection scope of the present application.

[0168] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this application will not further describe various possible combinations.

[0169] In addition, the various implementation modes of the present application may be arbitrarily combined, and as long as they do not violate the concept of the present application, they should also be regarded as the contents disclosed in the present application.

Claims

1. A method for preparing an adsorbent based on X molecular sieve, comprising the following steps: 1) mixing the X molecular sieve with a binder, forming and calcining to obtain a formed body; 2) treating the molded body obtained in step 1) with an alkaline solution to in-situ crystallize the binder therein to obtain a crystallized product; 3) performing ion exchange on the crystallized product obtained in step 2) with an ammonium salt solution, and calcining the product under a flowing atmosphere to obtain a calcined product; and 4) The calcined product obtained in step 3) is subjected to barium ion exchange and optionally potassium ion exchange, and then dried to obtain the adsorbent.

2. The method according to claim 1, wherein in step 1): The X molecular sieve used has a SiO2 / Al2O3 molar ratio of 2.0-2.6, preferably 2.2-2.4, a particle size of 0.8-2.5 μm, preferably 0.8-1.5 μm, and preferably, based on Na2O, the Na mass fraction of the X molecular sieve is 15.0-17.0%; The binder used is selected from kaolinite, dickite, pearlite, refractory stone, halloysite, hydromica, montmorillonite, or a combination thereof. Preferably, the binder used is composed of 75-95% by mass of kaolinite and 5-15% by mass of halloysite; The mass ratio of the X molecular sieve to the binder is 80:20 to 99:1, preferably 95:5 to 99:1; The forming is ball forming; and / or The calcination temperature is 500-700° C., and the calcination time is 2.0-6.0 hours.

3. The method according to claim 1 or 2, wherein in step 2): The alkaline solution used is a mixed solution of sodium hydroxide and water glass, wherein the concentration of sodium hydroxide is 1.2-4.0 mol / L, and the concentration of silicon dioxide is 6-20 g / L, preferably, the concentration of sodium hydroxide is 1.2-2.0 mol / L, and the concentration of silicon dioxide is 10-15 g / L; In the alkaline solution treatment, the liquid-to-solid volume ratio of the alkaline solution to the formed body is 1.2-3.0:1, preferably 1.2-2.0:1; and / or The conditions for the alkaline solution treatment include: The treatment temperature is 90-100°C and the treatment time is 1.5-6.0h.

4. The method according to any one of claims 1 to 3, wherein in step 3): The ammonium salt is selected from ammonium chloride, ammonium sulfate, ammonium nitrate, or a combination thereof; The concentration of the ammonium salt solution is 0.2-5.0 mol / L, preferably 0.2-2.0 mol / L; The liquid-to-solid volume ratio of the ammonium salt solution to the crystallized product during the ion exchange process is 2-10:1, preferably 2-5:1; and / or The conditions for the ion exchange include: The temperature is 25-95°C, preferably 50-75°C, and the time is 0.5-5.0h, preferably 0.5-2.0h.

5. The method according to any one of claims 1 to 4, wherein during the roasting process of step 3): The calcination temperature is 100-500°C, preferably 100-300°C; The calcination time is 0.5-6.0h, preferably 2.0-4.0h; The flowing atmosphere is a flowing air atmosphere or an inert flowing atmosphere, preferably a flowing air atmosphere; and / or The gas flow rate of the flowing atmosphere is 0.1-1.5 L / h / g adsorbent.

6. The method according to any one of claims 1 to 5, wherein in step 4): The barium ion exchange is carried out with a solution of a soluble barium salt, preferably the soluble barium salt is selected from barium chloride, barium nitrate, or a combination thereof; The potassium ion exchange is carried out with a potassium salt solution, preferably the potassium salt is selected from potassium chloride, potassium nitrate, or a combination thereof; The barium ion exchange and potassium ion exchange are performed using a mixed solution comprising a soluble barium salt and a potassium salt; and / or The conditions for the barium ion exchange and optional potassium ion exchange include: The temperature is 30-95°C, preferably 80-95°C, the time is 2.0-48.0h, preferably 12.0-36.0h, and the volume space velocity is 1.0-10.0h -1 , preferably 1.0-3.0h -1 .

7. An adsorbent based on X molecular sieve, comprising 98.0-99.0 mass % of X molecular sieve and 1.0-2.0 mass % of matrix, wherein the adsorbent has a micropore volume of 0.18-0.30 mL / g, preferably 0.24-0.30 mL / g, a mesopore volume of 0.01-0.1 mL / g, preferably 0.01-0.05 mL / g, a mesopore maximum pore size of 2.0-8.0 nm, preferably 2.0-5.0 nm, a 250N compressive crushing rate of less than 5.5%, and a basic bulk density of 0.91-1.20 g / cm 3 .

8. The adsorbent according to claim 7, wherein at least part of the cationic sites of the X molecular sieve are occupied by barium and / or potassium ions, and based on the weight of the adsorbent, the Ba content in the adsorbent calculated as BaO is 38.0-41.0 mass %, and the K content in the adsorbent calculated as KO is 0-3.0 mass %.

9. The adsorbent according to claim 7 or 8, wherein 29 Si and 27 According to Al high-resolution magic angle nuclear magnetic resonance measurement, the sum of Si(OAl)4 and Si(OSi)1(OAl)3 structure tetrahedrons in the skeleton structure of the adsorbent accounts for a relative content of not less than 60 mol%, preferably not less than 70 mol% of the total silicon species, and the relative content of non-skeleton aluminum accounts for not more than 5 mol%, preferably not more than 3 mol%.

10. The adsorbent according to any one of claims 7 to 9, wherein the micropore specific surface area of ​​the adsorbent is 400-650 m 2 / g, external specific surface area is 1-30m 2 / g, and the average particle size D50 is 425-600μm.

11. The adsorbent according to any one of claims 7 to 10, prepared by the method according to any one of claims 1 to 6.

12. Use of the adsorbent according to any one of claims 7 to 11 for adsorption separation of p-xylene.

13. A method for adsorptive separation of p-xylene from mixed C8 aromatic hydrocarbons containing p-xylene by liquid phase adsorption separation, comprising the steps of contacting the mixed C8 aromatic hydrocarbons with an adsorbent described in any one of claims 7 to 11 to adsorb p-xylene, and contacting the adsorbent after adsorbing p-xylene with a desorbent to desorb p-xylene.

14. The method according to claim 13, wherein the desorbent is selected from p-diethylbenzene, toluene, or a combination thereof.

15. The method according to claim 13 or 14, wherein the operating pressure of the adsorption separation is 0.3-1.5 MPa and the operating temperature is 120-190°C.